Gallic acid mitigates high-fat and high-carbohydrate diet-induced steatohepatitis by modulating the IRF6/PPARγ signaling pathway - Qiu, Jiahao; Fu, Lihong; Xue, Yan; Yang, Yilan; Qiao, Fengjie; Zhu, Wanchun; Gao, Yating; Fang, Miao; Liu, Yufei; Gao, Zhujun; Guan, Yunfeng; Gao, Yueqiu; et al. (Frontiers in Pharmacology, 2025)
Gallic acid (GA), a natural organic phenolic compound, is an abundant plant food bioactive substance present in many medicinal herbs. GA has anti-oxidative, anti-inflammatory and anticancer activities on multiple metabolic disorders. The present study was carried out to uncover the alleviating effects of GA on metabolic dysfunction-associated steatohepatitis (MASH) and the underlying mechanisms of its action. In this study, a mouse model of MASH induced by high-fat and high-carbohydrate diet was used to test the impact of GA on metabolic disorders. We found that GA administration attenuated obesity and fatty liver, relieved insulin resistance, and mitigated hepatic steatosis, inflammation and liver injury. Transcriptome sequencing (RNA-seq) of mouse liver tissues identified 154 differentially expressed genes (DEGs) among the NCD, HFHC, and GA groups. Bioinformatic analysis of these DEGs revealed significant enrichment in lipid metabolism function and the PPARγ signaling pathway, which were further validated. Overexpression of PPARγ significantly reduced the therapeutic effect of GA both in vitro and in vivo. Notably, the transcription factor interferon regulatory factor 6 (IRF6), a protective factor in metabolic stress, which was predicted as the upstream regulator, was significantly upregulated by GA. Furthermore, it was verified that GA’s anti-lipid deposition effect depends on the negative regulation of IRF6 on PPARγ using knocking-down strategy. Taken together, GA increases hepatic IRF6 expression, which mitigates lipid accumulation of hepatocytes and subsequent liver damage via inhibiting the PPARγ signaling pathway. These findings suggest a novel strategy for MASH management based on pharmacological intervention with GA.